Effects of microhabitat temperature on escape behavior in the diurnal gecko, Gonatodes albogularis (Duméril & Bribon, 1836) (Squamata: Sauria: Sphaerodactylidae) - Domínguez López, Moisés E. (2015)
The present study examined the effect of microhabitat air temperature on the escape behavior of Gonatodes albogularis (Duméril & Bribon, 1836) in a tropical dry forest relict of Colombia, south america. results showed negative correlation between both microhabitat air temperature and distance between lizards and predators at the moment in which escape is triggered and between temperature and distance of lizards to the closest shelter.